Chemical strengthening additive of microcrystalline glass for dentistry, preparation method of chemical strengthening additive and chemical strengthening salt bath

Chemical strengthening is solved by using chemical strengthening additives composed of SiO2, Al2O3, Na2O, K2O and ZrO2, the problem of insufficient strength of dental microcrystalline glass is significantly improved, and its mechanical properties and biocompatibility are extended, and the use of molten salt is extended. Lifespan and the recycling of resources is realized.

CN119143394APending Publication Date: 2024-12-17深圳市昊迦科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411293351.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The strength and brittleness of the existing dental microcrystalline glass are insufficient, which cannot meet the production needs of single crowns of the posterior teeth, and the existing chemical strengthening process is not ideal.

Method used

Using chemical strengthening additives composed of SiO2, Al2O3, Na2O, K2O and ZrO2, the mechanical properties and biocompatibility of microcrystalline glass are improved by directionally releasing large radius ions and absorbing small radius ions in one direction, and the mechanical properties and biocompatibility of microcrystalline glass are improved by using chemical strengthening salt bath. Ion exchange enhancement.

Benefits of technology

It significantly improves the flexural strength, fracture toughness and hardness of dental microcrystalline glass, extends the service life of molten salt, reduces production costs and safety risks, and realizes the recycling of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a chemical strengthening additive for dental microcrystalline glass, a preparation method thereof and a chemical strengthening salt bath, the chemical strengthening additive is composed of SiO2, Al2O3, Na2O, K2O and ZrO2, the chemical strengthening additive comprises the following components by mole percentage: 15% < = Na2O + K2O < = 55%, 45% < = SiO2 < = 85%, 0% < = Al2O3 < = 20%, 0% < = ZrO2 < = 3%, and the sum of the mole percentages of the components is 100%. The additive provided by the invention can further enhance various mechanical property indexes of exchanged microcrystalline glass for dentistry; the service life of the molten salt can be prolonged, meanwhile, harmful substances cannot be introduced, the biocompatibility of the dental microcrystalline glass cannot be affected, and the surface of the microcrystalline glass cannot be damaged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microcrystalline glass preparation, and in particular to a chemical strengthening additive for dental microcrystalline glass, a preparation method thereof, and a chemical strengthening salt bath. Background Art

[0002] Teeth are an important part of the human body, and most people's teeth face problems such as caries, accidental tooth loss, acid-base corrosion, etc. As people's awareness of prevention continues to increase and repair methods continue to increase, the selection of appropriate repair materials with high strength, optimal biocompatibility, excellent corrosion resistance, wear resistance and certain aesthetic effects to repair and decorate teeth (commonly known as "false teeth") can restore the mechanical properties, biological functions and aesthetic effects of teeth.

[0003] At present, the strength and brittleness of most dental glass-ceramics on the domestic market cannot meet the requirements for the production of posterior single crowns, which limits its development. In order to improve the mechanical properties of dental glass-ceramics, such as surface hardness, bending strength and fracture toughness, most of them are adjusted from the formula ingredients of glass-ceramics, trying to continuously adjust the formula to increase the mechanical performance parameters of dental glass-ceramics. However, the results are minimal. At the same time, since the formula for preparing dental glass-ceramics basically contains Li + and Na + In recent years, methods and processes have emerged to use ion exchange chemical strengthening technology to improve the mechanical properties of dental microcrystalline glass for this type of small radius ions, but the results are not ideal.

[0004] Therefore, the prior art needs to be further improved and enhanced. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a chemical strengthening additive for dental glass-ceramics and a preparation method thereof, and a chemical strengthening salt bath, aiming to enhance the mechanical properties, chemical stability and biocompatibility of dental glass-ceramics.

[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0007] In a first aspect, a chemical strengthening additive for dental glass-ceramics, wherein the chemical strengthening additive is composed of SiO2, Al2O3, Na2O, K2O and ZrO2, wherein, in mole percentage, 15%≤Na2O+K2O≤55%, 45%≤SiO2≤85%, 0%≤Al2O3≤20%, 0%≤ZrO2≤3%, and the sum of the mole percentages of the components is 100%;

[0008] The dental glass-ceramics are strengthened by using the chemical strengthening additive, and the mechanical performance parameters of the strengthened dental glass-ceramics are improved by 5 to 30% compared with those without using the chemical strengthening additive; wherein the mechanical performance parameters include bending strength, fracture toughness and hardness.

[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0010] As a preferred technical solution, a chemical strengthening additive for dental microcrystalline glass is provided, wherein, in molar percentage, 15%≤Na2O+K2O≤25%, 55%≤SiO2≤70%, 5%≤Al2O3≤15%, 1%≤ZrO2≤2%, and the sum of the molar percentages of each component is 100%.

[0011] As a preferred technical solution, a chemical strengthening additive for dental glass-ceramics, wherein the crystal form in the dental glass-ceramics is mainly one or more of petalite, lithium silicate, β-spodumene, spinel, triclinic nepheline, sodium nepheline or β-quartz solid solution.

[0012] As a preferred technical solution, a chemical strengthening additive for dental glass-ceramics is provided, wherein the chemical strengthening additive has the performance of directionally releasing large-radius ions, unidirectionally absorbing small-radius ions, and maintaining the effective ion concentration participating in the chemical strengthening ion exchange of the glass-ceramics in the chemical strengthening salt bath.

[0013] As a preferred technical solution, a chemical strengthening additive for dental glass-ceramics, wherein when the chemical strengthening additive is deactivated, it can be used as a raw material for the production of lithium batteries and glass. The deactivation means that the chemical strengthening additive loses its chemical strengthening performance after use.

[0014] In a second aspect, a chemical strengthening salt bath is provided, wherein the chemical strengthening salt bath comprises: a molten salt and a chemical strengthening additive; the chemical strengthening additive is the chemical strengthening additive described above.

[0015] As a preferred technical solution, the chemical strengthening salt bath, wherein the molten salt is selected from one or more of sodium nitrate, potassium nitrate, lithium nitrate, sodium chloride, potassium chloride, sodium sulfate, and potassium sulfate.

[0016] As a preferred technical solution, in the chemical strengthening salt bath, the mass proportion of the chemical strengthening additive in the chemical strengthening salt bath is 1-10%.

[0017] In a third aspect, a method for preparing the chemical strengthening additive for dental glass-ceramics according to the first aspect, comprising:

[0018] Weighing corresponding raw materials according to the ratio, mixing the raw materials, melting and molding the mixed raw materials to obtain the chemical strengthening additive for dental glass-ceramics;

[0019] When the melt treatment is performed, the melting temperature is 1200 to 1680° C. and the time is 2 to 8 hours.

[0020] As a preferred technical solution, the method for preparing the chemical strengthening additive for dental microcrystalline glass, wherein during the molding process, the molding methods include: water quenching molding, roller molding, float molding, draw-down molding, and casting molding.

[0021] Beneficial effects: Compared with the prior art, the additive provided by the present invention can further enhance the mechanical performance indicators of the dental microcrystalline glass after exchange; it can extend the service life of the molten salt without introducing harmful substances and affecting the biocompatibility of the dental microcrystalline glass; while accelerating the chemical strengthening ion exchange, the additive will not add harmful ions to the molten salt and the microcrystalline glass, protect the surface of the microcrystalline glass from corrosion, and will not cause damage to the surface of the microcrystalline glass; it can extend the service life of the molten salt, reduce the dangerous operation of the salt bath replacement process, and ensure production safety; reduce the production cycle delay caused by the replacement of the salt bath, and improve production efficiency; at the same time, it also reduces the input of new salt bath materials and reduces production costs. The chemical strengthening additive that loses its activity can also be recycled to achieve the purpose of saving resources and recycling. DETAILED DESCRIPTION

[0022] The present invention provides a chemical strengthening additive for dental glass-ceramics and a preparation method thereof, and a chemical strengthening salt bath. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0023] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various embodiments. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. The serial numbers assigned to the components herein, such as "first", "second", etc., are only used to distinguish the objects described and do not have any order or technical meaning.

[0024] The inventors found that the strength and brittleness of most existing dental glass-ceramics cannot meet the requirements for the production of single crowns. In order to improve the strength and brittleness of dental glass-ceramics, they often adjust the formula of glass-ceramics and try to continuously adjust the formula to increase the mechanical performance parameters of dental glass-ceramics. However, the results are minimal. Domestic patents (CN106986556A, CN101921054A, etc.) have been applied for adding K2CO3, KCl, KOH, and Na3PO4 as auxiliary reagents, which can improve the surface stress and stress layer depth of glass after chemical strengthening, but it is mainly used in industrial glass. Since industrial glass and dental glass-ceramics have different components and purities, from the perspective of biocompatibility, it cannot be used to strengthen dental glass-ceramics; moreover, KOH auxiliary reagents have certain toxicity, which is harmful to the human body. From a safety perspective, it cannot be used to strengthen dental glass-ceramics; in addition, adding Na3PO4 auxiliary reagents will make the performance of glass-ceramics unstable after chemical strengthening ion exchange, and often exceed the lower limit of mechanical performance indicators, which is not suitable for dental glass-ceramics to improve mechanical properties. Although dental glass-ceramics has been widely used, the strength after chemical strengthening cannot meet the requirements, which limits its development.

[0025] In order to solve the above problems, the inventors of the present invention provide a chemical strengthening additive for dental glass-ceramics, wherein the chemical strengthening additive is composed of SiO2, Al2O3, Na2O, K2O and ZrO2, wherein, in molar percentage, 15%≤Na2O+K2O≤55%, 45%≤SiO2≤85%, 0%≤Al2O3≤20%, 0%≤ZrO2≤3%, and the sum of the molar percentages of each component is 100%. Among them, the role of SiO2 is to serve as the forming body oxide of the additive, which is an indispensable component of the additive structure. The role of Al2O3 is the intermediate oxide formed by the additive, which can improve the chemical stability of the additive. The roles of Na2O and K2O are important participating elements participating in ion exchange chemical strengthening to obtain dental glass-ceramics. By removing the K2O with a large ion radius in the molten salt bath, the K2O with a large ion radius in the molten salt bath is removed. + Compared with the Na+ ions with small ionic radius in glass-ceramics + The exchange reaction can generate surface compressive stress on the surface of the microcrystalline glass, further improving the monomer strength and scratch resistance of the microcrystalline glass. The role of ZrO2 is to improve the acid and alkali corrosion resistance of the additive. The additive can efficiently achieve the directional release of large-radius ions and unidirectional absorption of small-radius ions, thereby increasing or maintaining the effective ion concentration participating in the chemical strengthening ion exchange of the microcrystalline glass in the chemical strengthening salt bath molten salt.

[0026] In one implementation of the present invention, the chemical strengthening additive is used to treat the glass phase containing small radius ions Li + and Na +When chemically strengthening dental glass-ceramics, the use of the additive can improve the mechanical performance parameters such as bending strength, fracture toughness and hardness of the dental glass-ceramics by 5% to 30% compared with the case where no additive is used. The additive further enhances the strength of the dental glass-ceramics without introducing harmful substances and affecting the biocompatibility of the dental glass-ceramics.

[0027] In one implementation of the present invention, in terms of molar percentage, 15%≤Na2O+K2O≤25%, 55%≤SiO2≤70%, 5%≤Al2O3≤15%, 1%≤ZrO2≤2%, and the sum of the molar percentages of the components is 100%.

[0028] In one implementation of the present invention, the crystal form of the dental glass-ceramics is mainly one or more of petalite, lithium silicate, β-spodumene, spinel, triclinic nepheline, nautilite or β-quartz solid solution. That is to say, the crystal form of the dental glass-ceramics is mainly petalite, lithium silicate, β-spodumene, spinel, triclinic nepheline, nautilite or β-quartz solid solution, and the main crystal form of the glass-ceramics is one or more of petalite, lithium silicate, β-spodumene, spinel, triclinic nepheline, nautilite or β-quartz solid solution.

[0029] Based on the same inventive concept, the present invention also provides a chemical strengthening salt bath containing the above-mentioned chemical strengthening additive, wherein the molten salt is selected from one or more of sodium nitrate, potassium nitrate, lithium nitrate, sodium chloride, potassium chloride, sodium sulfate, and potassium sulfate.

[0030] In one implementation of the present invention, the additive with a mass proportion of 1 to 10 wt% is added to a molten salt with a sodium ion concentration greater than 250,000 ppm, and after reacting at 400 to 500° C. for 4 to 12 hours, the change in the sodium ion concentration in the molten salt is less than 1,000 ppm, and the lithium ion concentration is maintained between 10 and 300 ppm. The additive can further enhance the mechanical properties of dental microcrystalline glass and extend the service life of the molten salt.

[0031] Furthermore, after the chemical strengthening additives have been used up and become ineffective, the additives can be recovered and purified, and are an excellent raw material for lithium battery and glass production, achieving the purpose of saving resources and recycling.

[0032] Based on the same inventive concept, the present invention also provides a method for preparing the chemical strengthening additive for dental glass-ceramics, comprising: weighing corresponding raw materials according to a ratio, mixing the raw materials, melting and molding the mixed raw materials to obtain the chemical strengthening additive for dental glass-ceramics.

[0033] Specifically, the corresponding compound raw materials of SiO2, Al2O3, Na2O, K2O and ZrO2 are fully mixed in a certain proportion, the mixture is poured into a crucible, and heated at 1200-1680°C for 2-8 hours to make it molten. The molten additive is formed by water quenching, roller pressing, float method, pull-down, casting and other molding methods to obtain granular or flake shapes.

[0034] A chemical strengthening additive for dental glass-ceramics and a preparation method thereof, the data in the following tables are respectively: the chemical composition, melting time and temperature, and water quenching temperature of each embodiment are shown in Table 1, and the properties of dental glass-ceramics after strengthening with different additives are shown in Table 2. The specific steps are as follows:

[0035] 1. Preparation of additives

[0036] According to the composition of the additives in Table 1, the corresponding raw materials, SiO2, Al2O3, Na2O, K2O and ZrO2, are weighed, wherein, in mole percentage, 15%≤Na2O+K2O≤55%, 45%≤SiO2≤85%, 0%≤Al2O3≤20%, 0%≤ZrO2≤3%, and the sum of the mass percentages of each component is 100%;

[0037] Then, the corresponding raw materials of SiO2, Al2O3, Na2O, K2O and ZrO2 are fully mixed in a certain proportion;

[0038] The mixed mixture is poured into a crucible and molten according to the melting temperature of 1200-1680°C and the melting time of 2-8h in Table 1. The molten mixture is directly poured into water with a quenching temperature of 5-80°C in Table 1 for water quenching to obtain a granular additive, and the molten mixture is cooled to 500-1000°C and formed by stretching or rolling to obtain a sheet-like additive.

[0039] 2. Molten salt configuration

[0040] According to the molten salt composition shown in Table 2, analytically pure chemical raw materials are selected to prepare the molten salt. After preparation, it is necessary to grind to ensure that the molten salt components are fully mixed to obtain molten salt powder for ion exchange.

[0041] 3. Ion exchange strengthening

[0042] Place the prepared molten salt powder for ion exchange into the strengthening furnace, pay attention to the height of the molten salt liquid level, and the molten salt liquid level should be below 5 cm from the highest liquid level limit of the strengthening furnace; then spread the prepared additives evenly in layers on a stainless steel mesh carrier, and pay attention to placing them slowly and gently in the molten salt to ensure that the upper and lower surfaces of the dental glass-ceramics are in contact with the molten salt. After preheating for 30 min together with the dental glass-ceramics, perform ion exchange strengthening according to the strengthening temperature and strengthening time in Table 2.

[0043] 4. Removal of molten salt

[0044] After the ion exchange is completed, the strengthened dental glass-ceramics must be immediately transferred from the molten salt for ion exchange to a clean alumina crucible preheated at the same strengthening temperature and cooled with the furnace. When the temperature is lower than 50°C, the strengthened dental glass-ceramics can be taken out and then washed with running water for more than 30 minutes to ensure that there is no molten salt residue on the surface of the strengthened dental glass-ceramics.

[0045] The above embodiment can be tested according to the following method:

[0046] (1) Bending strength

[0047] The sample to be tested was prepared into a sheet (25×4×2mm) using a low-speed cutting device and a grinding device, and the surface of the glass sample was polished using iron oxide. The bending strength of the sample was tested using a universal strength tester using a three-point bending test method. The instrument loading speed is 1mm / min, the span is 20mm, and the maximum load can be obtained when the glass is broken. The bending strength of the sample can be calculated using the formula, which is as follows:

[0048]

[0049] Where M is the three-point bending strength (MPa), W is the maximum load (N), l is the span (mm), b is the sample width (mm), and d is the sample thickness (mm). The bending strength of the sample can be obtained through calculation.

[0050] (2) Vickers hardness test

[0051] Use a digital microhardness tester to test. Each group of samples tested has no less than 5 test points. The test pressure is 100gf, and the pressure is maintained for 10s. The hardness HV of the sample is calculated based on the size of the indentation caused by the indenter on the sample. The formula is as follows:

[0052]

[0053] Where HV is the microhardness value, F is the applied pressure, d 2 is the indentation area.

[0054] In order to test the effectiveness of the method of the present invention, the present invention selects lithium disilicate glass-ceramics for testing, but is not limited to this type of glass-ceramics. As can be seen from Table 2, the dental glass-ceramics without additives (as shown in the comparative example in Table 2) has a significantly lower mechanical property enhancement effect on the dental glass-ceramics than the dental glass-ceramics with additives (as shown in Examples 1-7 in Table 2) after ion exchange at the same time and temperature.

[0055] In Example 1-7, 1 to 10 wt% of the additive was added and fully reacted at 450 ° C for 12 hours. It was found that the change in the sodium ion concentration in the molten salt was less than 1%, and the lithium ion concentration was maintained between 0 and 150 ppm, while the additive was not used in the comparative example, and the lithium ion was seriously exceeded, which shows that the additive of the present invention can efficiently realize the directional release of large-radius ions and the unidirectional absorption of small-radius ions, thereby achieving the purpose of maintaining the concentration of lithium and sodium ions in the chemically strengthened salt bath molten salt. In addition, the use of the additive can increase the bending strength, fracture toughness and hardness of the dental glass-ceramics by 5% to 30% compared to when it is not used, and will not reduce the transmittance of the dental glass-ceramics, will not change the color of the dental glass-ceramics, and the strengthening is not limited by the shape of the dental glass-ceramics, and can significantly increase the mechanical properties of the dental glass-ceramics. Through the strengthening of the present invention, the bending strength of the dental glass-ceramics is above 427 ± 20MPa, and the Vickers hardness is above 554 ± 20HV (as shown in Table 2). The Vickers hardness of the dental glass-ceramics strengthened with additives in Examples 1-7 is significantly higher than that of the control group without additives, and all of them are increased by more than 50 HV compared with the group without additives.

[0056] Table 1

[0057] Example 1 Example 2 Example 3 Example 4 Example 5 Additive code T1 T2 T3 T4 T5 <![CDATA[SiO2]]> 50% 57% 78% 70% 63% <![CDATA[Al2O3]]> 10% 13% 4% 6% 5% <![CDATA[Na2O]]> 10% 8% 15% 6% 23% <![CDATA[K2O]]> 29% 20% 3% 17% 8.5% <![CDATA[ZrO2]]> 1% 2% 0 1% 0.5% Melting temperature 1350℃ 1500℃ 1680℃ 1600℃ 1550℃ Melting time 8h 5h 3h 4h 2h Water quenching temperature 5℃ 65℃ 50℃ 25℃ 30℃

[0058] Table 2

[0059]

[0060] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A chemical strengthening additive for dental glass-ceramics, characterized in that: The chemical strengthening additive is composed of SiO2, Al2O3, Na2O, K2O and ZrO2, wherein, in terms of mole percentage, 15%≤Na2O+K2O≤55%, 45%≤SiO2≤85%, 0%≤Al2O3≤20%, 0%≤ZrO2≤3%, and the sum of the mole percentages of the components is 100%; The chemical strengthening additive is used to strengthen the dental glass-ceramics, and the mechanical property parameters of the strengthened dental glass-ceramics are improved by 5 to 30% compared with those without the chemical strengthening additive.

2. The chemical strengthening additive for dental glass-ceramics according to claim 1, characterized in that: In terms of molar percentage, 15%≤Na2O+K2O≤25%, 55%≤SiO2≤70%, 5%≤Al2O3≤15%, 1%≤ZrO2≤2%, and the sum of the molar percentages of each component is 100%.

3. The chemical strengthening additive for dental glass-ceramics according to claim 1, characterized in that: The crystal form of the dental glass-ceramics is mainly one or more of petalite, lithium silicate, β-spodumene, spinel, triclinic nepheline, sodium nepheline or β-quartz solid solution.

4. The chemical strengthening additive for dental glass-ceramics according to claim 1, characterized in that: The chemical strengthening additive has the performance of directionally releasing large-radius ions, unidirectionally absorbing small-radius ions, and maintaining the effective ion concentration participating in the chemical strengthening ion exchange of the microcrystalline glass in the chemical strengthening salt bath.

5. The chemical strengthening additive for dental glass-ceramics according to claim 1, characterized in that: When the chemical strengthening additive is inactivated, it can be used as a raw material for the production of lithium batteries and glass.

6. A chemical strengthening salt bath, characterized in that: The chemical strengthening salt bath comprises: a molten salt and a chemical strengthening additive; the chemical strengthening additive is the chemical strengthening additive according to any one of claims 1 or 2.

7. The chemical strengthening salt bath according to claim 6, characterized in that The molten salt is selected from one or more of sodium nitrate, potassium nitrate, lithium nitrate, sodium chloride, potassium chloride, sodium sulfate, and potassium sulfate.

8. The chemical strengthening salt bath according to claim 6, characterized in that The chemical strengthening additive in the chemical strengthening salt bath accounts for 1-10% by weight.

9. A method for preparing the chemical strengthening additive for dental glass-ceramics as claimed in claim 1, characterized in that: include: Weighing corresponding raw materials according to the ratio, mixing the raw materials, melting and molding the mixed raw materials to obtain the chemical strengthening additive for dental glass-ceramics; When the melt treatment is performed, the melting temperature is 1200 to 1680° C. and the time is 2 to 8 hours.

10. The method for preparing the chemical strengthening additive for dental glass-ceramics according to claim 9, characterized in that: During the molding process, the molding methods include: water quenching molding, roll forming, float forming, draw-down molding and casting molding.